A fast-growing cold skin abscess revealing disseminated Mycobacterium intracellulare infection in an HIV-infected patient. (June 2018) - Mendes-Bastos, Pedro; Brás, Susana; Carvalho, Rodrigo
A 66-year-old woman with HIV-1 infection recently commenced on antiretroviral therapy (CD4+ 25 cells/mm 3 was referred to the Dermatology Clinic the following month due to a well-demarcated nodule in the extensor surface of the left arm with evident fluctuation but only slight pain on palpation, with no increase in temperature. Surgical drainage was performed with aspiration of yellowish-green exudate, with no characteristic smell. In culture of cutaneous exudate, Mycobacterium intracellulare was isolated. Upon careful review of the laboratory tests that were in progress at discharge, the same agent was isolated in one of the bronchoalveolar lavage cultures. The diagnosis of cutaneous abscess caused by M. intracellulare from hematogenous dissemination of lung infection was made. The patient was treated with clarithromycin, ethambutol and rifabutin for 24 months. M. intracellulare species and Mycobacterium avium constitute the Mycobacterium avium–intracellulare complex (MAC), responsible for the majority of human infections by atypical mycobacteria. They are ubiquitous bacteria and MAC infection mainly affect immunocompromised patients, with M. intracellulare being isolated in <5% of HIV patients with MAC infection. Cutaneous infection is rare and may present clinically with erythematous plaques, chronic ulcers or abscesses. When present, skin involvement is usually secondary to pulmonary infection.